Trends in cutaneous malignant melanoma in Sweden 1997–2011: thinner tumours and improved survival among men. (5th February 2015) - Lyth, J.; Eriksson, H.; Hansson, J.; Ingvar, C.; Jansson, M.; Lapins, J.; Månsson‐Brahme, E.; Naredi, P.; Stierner, U.; Ullenhag, G.; Carstensen, J.; Lindholm, C.
Summary: Background: Both patient survival and the proportion of patients diagnosed with thin cutaneous malignant melanoma (CMM) have been steadily rising in Sweden as in most Western countries, although the rate of improvement in survival appears to have declined in Sweden at the end of the last millennium. Objectives: To analyse the most recent trends in the distribution of tumour thickness (T category) as well as CMM‐specific survival in Swedish patients diagnosed during 1997–2011. Methods: This nationwide population‐based study included 30 590 patients registered in the Swedish Melanoma Register (SMR) and diagnosed with a first primary invasive CMM during 1997–2011. The patients were followed through 2012 in the national Cause of Death Register. Results: Logistic and Cox regression analyses adjusting for age at diagnosis, tumour site and healthcare region were carried out. The odds ratio for being diagnosed with thicker tumours was significantly reduced ( P  <   0·001) and the CMM‐specific survival significantly improved in men diagnosed during 2007–2011 compared with men diagnosed during 1997–2001 (hazard ratio = 0·81; 95% confidence interval 0·72–0·91; P  <   0·001), while the corresponding differences for women were not significant. Women were diagnosed with significantly thicker tumours during 2002–2006 and a tendency towards decreased survival was observed compared with those diagnosed earlier (during 1997–2001) and later (during 2007–2011). Conclusions: In Sweden, the CMMs of men are detected earlier over time and this seems to be followed by an improved CMM‐specific survival for men. Women are still diagnosed with considerably thinner tumours and they experience a better survival than men. Abstract : What's already known about this topic? Patient survival and the proportion of thin cutaneous malignant melanoma (CMM) has been rising over time in most Western countries, although the corresponding rate of improvement of survival appears to have declined in Sweden at the end of the last millennium. What does this study add? Swedish nationwide time trends of tumour thickness in CMM have been analysed for the first time. A shift over time towards thinner CMMs for men was accompanied by a 19% improved 5‐year CMM‐specific survival. Corresponding changes were not observed for women, although a superior 5‐year CMM‐specific survival still exists compared with that of men, motivating a continued need for improved secondary preventive actions for men.